Program Kegiatan Praktik Pengalaman Lapangan (PPL) di UPT SD Negeri 2 Kekeri - Lestari, Tri Ayu; Pahmi, Saepul (Universitas Mataram, 2024)
Field Experience Practice (PPL) was conducted at UPT SD Negeri 2 Kekeri, starting on February 16, 2024, and concluding on May 22, 2024. This program provides a valuable opportunity for students to develop and strengthen their competencies in performing duties as professional educators in schools. The process of developing teaching skills for prospective teachers is pursued by applying the principles taught by Ki Hadjar Dewantara: niteni (observing), nirokke (imitating), and nambahi (developing). PPG students learn to develop their teacher identity and teaching process by integrating an analytical understanding of the context of a particular educational unit with the concepts and practices of other core courses. The students' practical experience is designed as a continuous improvement process through the lesson study format. Problems encountered in the field become part of the maturation process for students, while also providing opportunities to enhance their teaching abilities in the future.